The THE EFFECT OF ECONOMIC FREEDOMS ON PUBLIC DEBT IN TÜRKİYE - Üre, Salim; KARAKÖY, Çağatay (Journal of process management and new technologies, 2024)
While the fourth industrial revolution is happening at great speed, it is an inevitable fact that without significant economic investments, countries will enter a stagnant economy and lose their international competitiveness. Large amounts of funds are needed to invest in these areas. For this reason, countries that cannot provide sufficient funds through national and international trade need public borrowing to finance investments. Given these explanations, the study focused on analyzing a dataset encompassing the share of public debt in GDP and the sub-criteria of the economic freedom index for the years 1999-2022. The objective was to explore the influence of economic freedoms on the economy. Public debt in Türkiye ARDL (Autoregressive Distributed Lag) method was used to determine the short- and long-term relationship. According to the results of the analysis, business freedom and tax burden, which are the sub-criteria of economic freedom, have a positive effect on public expenditures; Monetary freedom, trade freedom, financial freedom and investment freedom have been found to have a negative impact. It is expected that these borrowings will turn into a burden on the country's economy in the short term and gain in the long term.